Innovative construction material technologies for sustainable and resilient civil infrastructure. (2022) - Soliman, Ahmed; Hafeez, Ghazanfarah; Erkmen, Emre; Ganesan, Rajamohan; Ouf, Mohamed; Hammad, Amin; Eicker, Ursula; Moselhi, Osama
Abstract: Construction material technologies are the driving force for enhancing and improving building and infrastructure functionality. Solutions for many challenges faced by the construction industry, such as low energy efficiency and high carbon emission, had sparkled from innovative construction materials technologies. Hence, selecting adequate construction materials will play an essential role in shaping the life cycle for infrastructure ("from cradle to cradle") and consequently the project cost. This paper illustrated that innovation in construction materials could occur on various levels, including compositions selection, production technology and end-of-life options. Hence, construction materials roles in achieving civil infrastructure sustainability extend beyond satisfying performance criteria to shaping their whole life cycle. This needs a shift in specifications and guidelines for materials selections, design and rehabilitation concepts for new and old infrastructure, and accurate prediction models to simulate the performance.